TAFSIR TARBAW?: WACANA KHALIFAH DAN KHIL?FAH DALAM REFORMASI PENDIDIKAN ISLAM HOLISTIK - Abd Aziz; Fatkhul Mubin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This study is intended to describe the discourse of the caliphate and caliphate in the reform of holistic Islamic education through holistic education. The goal of holistic Islamic education reform is to produce a generation of caliphs with the political thought of the caliphate as caliphs as individuals and groups who have the potential to fight for and realize "the welfare of secular profane life (duny?), as well as the welfare of sacred religious life (the hereafter), accompanied by safety. Human beings from all forms of suffering (al-n?r). Meanwhile, the purpose of establishing a state or caliphate in terms of education is to create prosperity. Therefore, what can guarantee the goal of the State is education, for the realization of benefit and welfare or prosperity is the application of universal principles as taught by Islam, namely the principle of justice in law enforcement, the principle of trust in carrying out duties, responsibilities, and professionalism.